Evaluation on customer adoption process and brand positioning for Scientige Sdn Bhd in 2007 / Norhaidah Ahmad - Ahmad, Norhaidah (Faculty of Business and Management, 2007)
Scientige Sdn Bhd is a company that involve in the oil, gas and petrochemical industry and the company offer various products and services in the field. Since the company is still new in the market ( 2 years in the field) , the company required to have strong brand positioning so that the client will see them as capable in doing business since business in oil and gas is tough and competition is really stiff.